An Overview of the Mechanisms Against “Candidatus Liberibacter asiaticus”: Virulence Targets, Citrus Defenses, and Microbiome - Yang, Chuanyu; Ancona, Veronica (Frontiers in Microbiology, 2022)
Citrus Huanglongbing (HLB) or citrus greening, is the most destructive disease for citrus worldwide. It is caused by the psyllid-transmitted, phloem-limited bacteria ‘Candidatus Liberibacter asiaticus’ (CLas). To date, there are still no effective practical strategies for curing citrus HLB. Understanding the mechanisms against CLas can contribute to the development of effective approaches for combatting HLB. However, the unculturable nature of CLas has hindered elucidating mechanisms against CLas. In this review, we summarize the main aspects that contribute to the understanding about the mechanisms against CLas including 1) CLas virulence targets, focusing on inhibition of virulence genes; 2) activation of citrus host defense genes and metabolites of HLB-tolerant citrus triggered by CLas, and by agents; 3) we also review the role of citrus microbiome in combatting CLas. Finally, we discuss novel strategies to continue studying mechanisms against CLas and the relationship of above aspects.